2006
DOI: 10.1111/j.1365-2141.2006.06194.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Burkitt lymphoma in due time: a practical approach

Abstract: Summary The quick diagnosis of Burkitt lymphoma (BL) and its clear‐cut differentiation from diffuse large B‐cell lymphoma (DLBCL) is of great clinical importance because treatment strategies for these two disease entities differ markedly. As these two lymphomas are difficult to distinguish using the current World Health Organization classification, we studied 39 cases of highly proliferative peripheral blastic B‐cell lymphoma (HPBCL) to establish a practical differential‐diagnostic algorithm. Characteristics s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…Previous studies have suggested that high proliferation fraction (Ki-67490%), typical Burkitt lymphoma immunophenotype (CD10 þ /bcl-6 þ /bcl-2 À ), and a CD38 þ / CD44 À /TCL-1 þ pattern may predict the presence of MYC rearrangement. [2][3][4][5] In this study, 87% of cases had a high Ki-67 (495%), and 83% of cases expressed TCL-1 and lacked CD44, which is in general consistent with these published results. However, the immunophenotype of CD10 þ /bcl-6 þ / bcl-2 À is mainly present in group I cases (89%) and at very low rate in group II cases (21%), implying that such immunophenotype may not be a reliable predictor in MYC-complex lymphomas.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Previous studies have suggested that high proliferation fraction (Ki-67490%), typical Burkitt lymphoma immunophenotype (CD10 þ /bcl-6 þ /bcl-2 À ), and a CD38 þ / CD44 À /TCL-1 þ pattern may predict the presence of MYC rearrangement. [2][3][4][5] In this study, 87% of cases had a high Ki-67 (495%), and 83% of cases expressed TCL-1 and lacked CD44, which is in general consistent with these published results. However, the immunophenotype of CD10 þ /bcl-6 þ / bcl-2 À is mainly present in group I cases (89%) and at very low rate in group II cases (21%), implying that such immunophenotype may not be a reliable predictor in MYC-complex lymphomas.…”
Section: Discussionsupporting
confidence: 91%
“…28 Recognition of MYC rearrangement is important because it portends a more aggressive disease and may prompt more timely and intensive therapy. 2,12 However, MYC-rearranged lymphomas may be underrecognized because karyotype and/or FISH analysis are not performed in all cases. Therefore, recognition of the features suggestive of MYC rearrangement may be important to prompt additional testing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations